From First Symptom To Comprehensive Care: A Multicenter Experience In Diagnosing And Managing Complex Pediatric Autoimmune Organopathies (The Review of Diabetic Studies, 2025)
Aim and background: Autoimmune organopathies pose significant and serious health risks for pediatric patients, necessitating comprehensive approaches to diagnosis and management. The aim of this extensive multicenter study, was to identify and categorize the initial clinical manifestations of these challenging organopathies.Material and methods This prospective cohort study examines children patients aged 2 to 18 with multi-system autoimmune organopathies, enrolling 50 participants from Al-Azhar University Hospitals between November 2024 and November 2025.  Blood samples were obtained at these intervals for multiple analyses, including complete blood count (CBC), complement levels, and immunoglobulins utilizing accredited assays.  Clinical outcomes, including readmission and complication rates, treatment responses, quality of life, and depression metrics, were assessed in conjunction with patient and guardian surveys.  Imaging studies were conducted according to disease phenotypes, and statistical analysis included repeated-measures ANOVA and further tests to confirm significance.  Minimal missing data were adequately resolved, ensuring sufficient power for detecting medium effect sizes.ResultsLaboratory results indicated elevated C3 and C4 levels, accompanied by a decrease in autoantibodies and IgG/IgA. Clinical outcomes were significant, with readmissions reduced from 22% to 9%, complications lowered from 17% to 7%, and treatment response improved to 84%. Moreover, quality of life metrics had a substantial increase, but the depression index exhibited a notable decline. Imaging modalities, including MRI, CT, and echocardiography, shown particular efficacy in patient evaluation, resulting in elevated stakeholder satisfaction about care coordination.ConclusionThe multicenter study aimed to identify and categorize clinical symptoms of organopathies, establish an organizational structure, record diagnostic timelines, and formulate criteria for diagnosis and treatment.